Butyryl-cholinesterase is related to muscle mass and strength. A new biomarker to identify elderly subjects at risk of sarcopenia - Cacciatore, Francesco; Della-Morte, David; Basile, Claudia; Curcio, Francesco; Liguori, Ilaria; Roselli, Mario; Gargiulo, Gaetano; Galizia, Gianluigi; Bonaduce, Domenico; Abete, Pasquale (Biomarkers in medicine, 2015)
To determine the relationship between Butyryl-cholinesterase (α-glycoprotein synthesized in the liver, b-CHE) and muscle mass and strength. Muscle mass by bioimpedentiometer and muscle strength by grip strength were evaluated in 337 elderly subjects (mean age: 76.2 ± 6.7 years) admitted to comprehensive geriatric assessment. b-CHE levels were lower in sarcopenic than in nonsarcopenic elderly subjects (p < 0.01). Linear regression analysis demonstrated that b-CHE is linearly related with grip strength and muscular mass both in men and women (r = 0.45 and r = 0.33, p < 0.01; r = 0.55 and r = 0.39, p < 0.01; respectively). Multivariate analysis confirms this analysis. b-CHE is related to muscle mass and strength in elderly subjects. Thus, b-CHE may be considered to be a fair biomarker for identifying elderly subjects at risk of sarcopenia.